Spanish Transcultural Adaptation of the Activity Card Sort - Cristina Alegre-Muelas; Jorge Alegre-Ayala; Elisabet Huertas-Hoyas; MªRosa Martínez-Piédrola; Jorge Pérez-Corrales; Nuria Máximo-Bocanegra; Carlos Sánchez-Camarero; Marta Pérez-de-Heredia-Torres (Occupational Therapy International)
The Activity Card Sort (ACS) measures the level of participation, as perceived by each person which, unlike other scales, makes it both personal and significant. However, there is a limitation to applying the ACS to Spanish older adults as it is restricted to culturally relevant activities solely in the United States. Therefore, the aim of this study was to select activity items that reflected Spanish older adults’ lifestyles in order to develop the Activity Card Sort-Spain Version (ACS-SP). Frequently, activities performed in Spain (n=103) were listed in an initial draft. The Likert scale was administrated to a large group of Spanish nationals over the age of 60 years (n=98) to establish which type of activities will be eventually included in the Spanish version. The final version was drawn up comprising 79 activities distributed between four performance areas. In addition, other activities that were not previously included by other assessment tools were considered and have been listed in this review, such as taking a nap, going out for a drink or “tapas,” or searching for a job. The gradual adaptation to ACS for Spaniards will make it possible to measure the level of an individual’s participation within a community. However, further work on psychometric properties is needed.